Desain Pengembangan Kurikulum Pendidikan Agama Islam Berpusat pada Bahan Ajar dan Peserta Didik - Qorimah; Muhammad Fathan Rizkiyyan; Khuriyah (Comit: Communication, Information and Technology Journal, 2025)
Islamic Religious Education is one education that has fairly important role in forming individuals into good people through the provision several spiritual values, formation morals, and character. The purpose writing is to analyze characteristics, structure and implementation as well advantages and disadvantages Islamic religious education curriculum that is centered on teaching materials and students. Writing method is to use qualitative type. Rresults and conclusions obtained (1) Characteristics use Islamic Religious Education curriculum that is centered on teaching materials, including, learning approach used uses the discovery or inquiry approach, students are encouraged to understand related to basic structure and logic, etc. While characteristics use Islamic Religious Education curriculum that is centered on students students as active learning subjects and application of constructivism theory; (2) Structure and implementation Islamic Religious Education curriculum is centered on teaching materials, feasibility studies, compiling initial concepts for curriculum planning, developing plans, conducting curriculum trials, implementing curriculum, conducting assessments, and implementing improvements. While structure and implementation Islamic religious education curriculum is centered students, namely including formulating objectives, determining curriculum content, selecting activities, and formulating evaluations; (3) There are advantages and disadvantages to each use Islamic religious education curriculum development design centered on teaching materials and students.